2020
DOI: 10.31234/osf.io/fwr3m
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impaired Evidence Accumulation as a Transdiagnostic Vulnerability Factor in Psychopathology

Abstract: There is substantial interest in identifying biobehavioral dimensions of individual variation that cut across heterogenous disorder categories, and computational models can play a major role in advancing this goal. In this report, we focused on efficiency of evidence accumulation (EEA), a computationally characterized variable derived from sequential sampling models of choice tasks. We created an EEA factor from three behavioral tasks in the UCLA Phenomics dataset (n=272), which includes healthy participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Beyond research on ADHD, reductions in EEA have been documented in schizophrenia (126,127), depression (128), individuals at risk for frequent substance use (129), and individuals with high levels of externalizing spectrum symptoms (130). Extending these findings, our recent work has provided direct evidence that EEA is a transdiagnostic risk factor for psychopathology (131). In a large patient sample drawn from the UCLA Consortium for Neuropsychiatric Phenomics (132) we found that a latent EEA factor derived from multiple tasks was substantially reduced in ADHD, schizophrenia, and bipolar disorder relative to healthy participants, and displayed a negative correlation with the overall severity of individuals' crossdisorder psychopathology symptoms.…”
Section: Reduced Eea As a Transdiagnostic Neurocognitive Risk Factor mentioning
confidence: 71%
“…Beyond research on ADHD, reductions in EEA have been documented in schizophrenia (126,127), depression (128), individuals at risk for frequent substance use (129), and individuals with high levels of externalizing spectrum symptoms (130). Extending these findings, our recent work has provided direct evidence that EEA is a transdiagnostic risk factor for psychopathology (131). In a large patient sample drawn from the UCLA Consortium for Neuropsychiatric Phenomics (132) we found that a latent EEA factor derived from multiple tasks was substantially reduced in ADHD, schizophrenia, and bipolar disorder relative to healthy participants, and displayed a negative correlation with the overall severity of individuals' crossdisorder psychopathology symptoms.…”
Section: Reduced Eea As a Transdiagnostic Neurocognitive Risk Factor mentioning
confidence: 71%
“…Additionally, neuromarkers of the type demonstrated here could one day find more direct clinical application. There is growing evidence that impaired neurocognitive abilities are associated with diverse forms of psychopathology [12][13][14][15][16] , including schizophrenia [53][54][55] , externalizing disorders such as ADHD 56,57 and substance use disorders 58,59 , and internalizing disorders such as depression 60,61 . Notably, in this same ABCD baseline sample, we recently showed 62 that reduced scores on the general factor of neurocognition were associated with elevation in the general factor of psychopathology [63][64][65] (widely terms the "P factor"), which confers vulnerability to nearly all prevalent psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences in these abilities are important because they are associated with diverse life outcomes. Better neurocognitive abilities are associated with health, well-being, and occupational success 10,11 , while deficits in neurocognition, and closely related constructs such as executive functioning 7,9 , are associated with a broad range of psychopathologies [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%